João Maria André, "Douta Ignorância. Linguagem e Diálogo. O poder e os limites da palavra em Nicolau de Cusa", Coimbra, Imprensa da Universidade de Coimbra, 2019, 451 pp. - Marcos dos Passos, Flávio (Filosofia, 2020)
Learned Ignorance. Language and Dialogue. The power and limits of the word in Nicholas of Cusa by João Maria André is a work that presents cusanian thinking from three thematic lines: Learned Ignorance, Language and Dialogue with a particular emphasis on the power and limits of word. In the first part dedicated to Learned Ignorance André demonstrates how Nicholas of Cusa theorized the notion of learned ignorance and outlines its anthropological dimensions. He demonstrates that it is a philosophy of interpretation that has three meanings: a hermeneutic, an ethical and an aesthetic. In the second part André focuses on the theme of Language, with emphasis on the hermeneutics of divine names in the tension between finitude and infinitude. In the third part entitled Dialogue the author approaches the coincidence of opposites and the concept of transumptio. He examines the relationship between the actions of listening and speaking and, finally, presents Nicholas of Cusa's legacy to globalized society.